Gigantic submandibular pleomorphic adenoma: A rare case report. (2019) - Abdelkhalek, Mohamed; Elmetwally, Mohamed; Mazy, Alaa; Gad, Mona; Elsaid, Ahmed; Awny, Shadi; Refky, Basel; Abdallah, Ahmed; Elalfy, Amr F.; Shokeir, Farida A.; Abdallah, Samar; Elfeky, Abeer; et al.
Highlights: Pleomorphic adenoma can attain huge sizes if neglected. It could cause facial disfigurement and compromise the airway. Surgical resection is the main stay of treatment. Abstract: Introduction: Pleomorphic adenoma (PA) is the most common benign salivary gland tumor. When neglected on some occasions, its size and weight can enormously augment. Case presentation: We report a case of a giant submandibular pleomorphic adenoma in a 75 years old female patient which measured 34 × 26 × 20 cm and weighed 8.1 kg. Conclusion: Neglecting such tumors without treatment, can cause severe facial disfigurement and can even hinder the airway.